Young adults' intention to use mobile payment in Malaysia - Chow, Alvin Mun Sing (2024)
This research aims to study the relationship between perceived risk, perceived trust, perceived ease of use and perceived usefulness towards the young adults’ intention to use mobile payment in Malaysia. The target respondents in this study are young adults who aged from 19 to 39 years old. Moreover, 216 sets of questionnaires were collected, but only 208 sets of questionnaires were valid. The data collected from the survey are analyzed using IBM Statistical Package for Social Science (SPSS) version 29. The respondents’ feedback was analyzed and presented using descriptive analysis, inferential analysis, Pearson’s correlation analysis, as well as Multiple Regression analysis.